Race, pain, and opioids among patients with chronic pain in a safety-net health system. (1st May 2021) - Haq, Nimah; McMahan, Vanessa M.; Torres, Andrea; Santos, Glenn-Milo; Knight, Kelly; Kushel, Margot; Coffin, Phillip O.
Highlights: Black participants had higher average pain and lower past year maximum opioid dose. Participants with past year injection drug use had lower odds of being Black. There was no difference by race in the use of opioid stewardship measures. There was no difference in opioid discontinuations for yellow flag events by race. Abstract: Background: Recent changes in opioid prescribing practices in the US may exacerbate disparities in opioid access among Black compared to White patients. Methods: To evaluate racial disparities in opioid prescribing and stewardship, we used baseline data collected from 2017 to 2019 for a longitudinal cohort of patients with chronic non-cancer pain and a history of illicit substance use. Sociodemographic characteristics, pain, psychological distress, substance use, and opioid prescription practices were compared between Black and White participants. We conducted multivariable logistic regression with race as the outcome. We also compared yellow flag events (opioid-related emergency department visits, illicit substances on urine drug screens, provider-documentation of concerning behaviors) by race. Results: Over half of participants analyzed were Black (57%) and the remainder White (43%). Participants with worse average pain in the past three months (adjusted odds ratio [AOR]:1.29, 95%CI:1.08−1.55, p = 0.006) had higher odds of being Black. Past-year injection drug use (AOR:0.39, 95%CI:0.16−0.94, p = 0.04) and a higher past-year maximum opioid dose (AOR per 10 morphine milligram equivalents (MME):0.99, 95%CI:0.98−1.00, p = 0.006) were associated with lower odds of being Black. We found no differences by race in the use of opioid stewardship measures or discontinuation of opioids based on yellow flag events. Conclusion: Lower past-year maximum MME dose, despite higher average pain and less injection drug use, may represent bias away from prescribing opioids for chronic pain among Black patients. This could be due to unmeasured implicit provider bias or patient-level factors (e.g., utilizing non-opioid pain coping strategies or being less likely to request additional opioids).